ТАСВИРИЙ САНЪАТ МАШҒУЛОТЛАРИДА САМАРАЛИ ТЕХНОЛОГИЯНИНГ ҚЎЛЛАНИЛИШИ - Абдирасилов, С.Ф. (SCIENCE and SOCIETY, 2021)
This article describes the methodology and organization of a master class in the art classes at school. It makes the lesson clear, vivid, memorable, which positively affects the aesthetic development of the younger generation, instills a love of fine art, the art of watercolor.